Perkembangan Konsep Negara Hukum dalam Perspektif Hukum Tata Negara - Thaher, Irmanjaya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The concept of the rule of law as the foundation of modern statecraft affirms the supremacy of law in governing national life. Encompassing both formal and substantive dimensions, the rule of law emphasizes the protection of human rights, limitations on government power, and guarantees of justice. This multidisciplinary study incorporates philosophical, sociological, political, and juridical perspectives that continue to evolve alongside global socio-political transformations. This research uses a Systematic Literature Review (SLR) to systematically, structured, and transparently identify, evaluate, and synthesize scholarly findings. This method examines scholarly articles on the evolution of the concept of the rule of law within the rechtsstaat and rule of law traditions and their implementation in the modern constitutional system, producing evidence-based conclusions while minimizing researcher bias. The research aims to analyze the development of the concept of the rule of law through an integration of theoretical and practical dimensions. It aims to identify structural challenges to implementation, explore the role of jurisprudence and judicial activism, evaluate legislative responsibility in producing just legal products, and deepen understanding of the philosophical foundations of the rule of law concept to address the complexities of contemporary legal realities. The findings indicate that the implementation of the rule of law in Indonesia faces legislative inconsistencies and political intervention that hinder effective law enforcement. Jurisprudence plays a crucial role in interpreting constitutional principles, but judicial activism requires balance to prevent judicial supremacy. Legislative power must produce laws that are formally valid and substantively just. The effectiveness of a state based on the rule of law requires reform of the legislative system, strengthening of public institutions, and developing a legal culture in society. The conclusion emphasizes the need for comprehensive reform of the legislative system, strengthening the capacity of public institutions, and developing a legal culture to address the gap between constitutional norms and the reality of implementation. A balance between judicial independence and accountability is necessary to prevent the overreach of judicial authority. The legislature is responsible for producing laws that protect citizens' rights in a contextualized manner. The concept of a state based on the rule of law requires in-depth philosophical understanding and ongoing theoretical reformulation to address the complexities of contemporary law.